2015
DOI: 10.4084/mjhid.2015.030
|View full text |Cite
|
Sign up to set email alerts
|

Nutritionally Variant Streptococci Bacteremia in Cancer Patients: a Retrospective Study, 1999-2014

Abstract: BackgroundNutritionally variant Streptococci (NVS), Abiotrophia and Granulicatella are implicated in causing endocarditis and blood stream infections more frequently than other sites of infection. Neutropenia and mucositis are the most common predisposing factors for infection with other pathogens in cancer patients. In this study, we investigated the clinical characteristics of NVS bacteremia in cancer patients and identified risk factors and outcomes associated with these infections.Materials and MethodsWe r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 22 publications
(29 reference statements)
0
8
0
1
Order By: Relevance
“…A relationship between periodontal inflammation and bacteremia has been reported in an observational study showing that patients with gingivitis/periodontitis more often developed bacteremia owing to coagulase-negative staphylococci and oral viridans streptococci during neutropenia than did those with a healthy periodontium ( p  = 0.047) [8]. A retrospective study showed that 61.5% of cancer patients with NVS bacteremia had mucositis or gingivitis [9]. In non-neutropenic patients, a previous report showed that the generalized presence of gingival bleeding after tooth brushing (which is a sign of gingivitis or periodontitis) was associated with an almost eightfold increase in the risk of bacteremia [10].…”
Section: Discussionmentioning
confidence: 92%
“…A relationship between periodontal inflammation and bacteremia has been reported in an observational study showing that patients with gingivitis/periodontitis more often developed bacteremia owing to coagulase-negative staphylococci and oral viridans streptococci during neutropenia than did those with a healthy periodontium ( p  = 0.047) [8]. A retrospective study showed that 61.5% of cancer patients with NVS bacteremia had mucositis or gingivitis [9]. In non-neutropenic patients, a previous report showed that the generalized presence of gingival bleeding after tooth brushing (which is a sign of gingivitis or periodontitis) was associated with an almost eightfold increase in the risk of bacteremia [10].…”
Section: Discussionmentioning
confidence: 92%
“…Several “indicator” genera of the highest IL‐1β quartile were low‐abundant phylotypes, previously documented in diverse opportunistic infections and immune subversion. Abiotrophia , a common oral genus earlier grouped under “nutritionally variant Streptococci ” is implicated in bacteremia and invasive infections (Senn et al., ; Yacoub et al., ). In the oral niche, supragingival Abiotrophia associated with leukemic status and indicated dysbiosis related to perturbed immune status (Wang et al, , ).…”
Section: Discussionmentioning
confidence: 99%
“…Abiotrophia, a common oral genus earlier grouped under "nutritionally variant Streptococci" is implicated in bacteremia and invasive infections (Senn et al, 2006;Yacoub et al, 2015). In the oral niche, supragingival…”
Section: Otu-representingmentioning
confidence: 99%
“…produces β-and α-galactosidase. The genus contains one species of Abiotrophia defectiva, which can cause bacteraemia, keratitis [38], oral mucositis and gingivitis [58], urinary tract infection [17] and infective endocarditis [15,17]. More commonly, Abiotrophia spp.…”
Section: Streptococci With Special Nutritional Requirementsmentioning
confidence: 99%